2019
DOI: 10.24925/turjaf.v7isp2.121-127.3174
|View full text |Cite
|
Sign up to set email alerts
|

Nohut (Cicer arietinum L.) Tarımında Gül Posası, Ahır Gübresi ve Bakteri Aşılamanın Verim ve Bazı Verim Öğelerine Etkileri

Abstract: The study was carried out to determine the effects of organic (rose pulp, barn fertilizer and bacterial inoculation) and chemical fertilizer applications on yield and yield components of chickpea varieties (Aydın 92, Azkan and Gökçe) in Dinar district of Afyonkarahisar province in 2011. The experimental design was split plot with three replications. In this research, plant height, first pod height, number of branches, pod and grains per plant, seed yield in plant, biological yield, grain yield, harvest index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…According to the LSD test results, PV2001, PV2002, and PV2003 genotypes were in the first group (group a), and the Riberia genotype was in the second group (group b) (Table 3). Aldemir (2019) reported that different fertilizer applications in the chickpea plant affected the seed yield in three different chickpea cultivars significantly and obtained a similar result to our analysis results. Göksu Küçük andCeyhan / Selcuk J Agr Food Sci, (2022) 36 (3): 501-506 (2012), because of his study on peas, reported that the fertilizers did not have effects on the cultivars and contradicted our result.…”
Section: Seeed Yieldsupporting
confidence: 89%
See 4 more Smart Citations
“…According to the LSD test results, PV2001, PV2002, and PV2003 genotypes were in the first group (group a), and the Riberia genotype was in the second group (group b) (Table 3). Aldemir (2019) reported that different fertilizer applications in the chickpea plant affected the seed yield in three different chickpea cultivars significantly and obtained a similar result to our analysis results. Göksu Küçük andCeyhan / Selcuk J Agr Food Sci, (2022) 36 (3): 501-506 (2012), because of his study on peas, reported that the fertilizers did not have effects on the cultivars and contradicted our result.…”
Section: Seeed Yieldsupporting
confidence: 89%
“…Bulut (2013) reported that the effects of grafting and fertilizer applications on the number of seeds per plant were important, and the mean value of the fertilizers varied between 25.08 -34.76 mumber per plant. Aldemir (2019), on the other hand, reported that he obtained the least seed yield from the control plot, as in our study.…”
Section: Number Of Seeds Per Plantsupporting
confidence: 76%
See 3 more Smart Citations